Preparation of Hydrochar from Salacca zalacca Peels by Hydrothermal Carbonization: Study of Adsorption on Congo Red Dyes and Regeneration Ability - Mauizatul Hasanah; Alfan Wijaya; Fitri Suryani Arsyad; Risfidian Mohadi; Aldes Lesbani (Science and Technology Indonesia, 2022)
Hydrochar of Salacca zalacca peels (HC-SP) is prepared by hydrothermal carbonization treatment of Salacca zalacca peels (SP) obtained from local fruits at Palembang, South Sumatera, Indonesia, with the resulting yield weight reaching 90%. Materials are characterized using the XRD diffraction, FTIR spectrum, and SEM-EDX. The XRD pattern shows the characteristics of the formation of amorphous compounds. The FTIR spectrum confirms the presence of functional groups O-H, C-H, C=C, and C-O. Data of SEM-EDX show that materials have heterogeneous morphologies, form aggregates, and in HC-SP materials there is an increase in carbon content from the initial material. The capacity of SP in the congo red (CR) adsorption process is 33.003 mg/g and increases to 133.333 mg/g in HC-SP. The maximum dye adsorbed was achieved at pH 4. The adsorption kinetics followed PSO with the equilibrium adsorption occurring at 90 minutes, and the adsorption isotherm followed the Langmuir isotherm with the value of R2 closer to the value of 1. A positive 4H value indicated that the adsorption is an endothermic process. In contrast, an 4S value suggested that the degree of irregularity in the adsorption process is small in large concentrations. Based on data regeneration ability, materials of SP and HC-SP can be used in the three cycles regeneration process of the CR adsorption process. The adsorption process of CR occurs physically and chemically based on enthalpy values and FT-IR data after being adsorbed with CR.